Inhibitory effect of calcium hydroxide combined with Nigella sativa against Enterococcus faecalis - Myrna Nurlatifah Zakaria; Yusfien Shabrina Putri; Asih Rahaju; Sri Fatmawati; Arief Cahyanto (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Calcium hydroxide is the gold standard medicament for root canal treatment. Enterococcus faecalis, the primary cause of intraradicular persistent endodontic infection, is often identified even after endodontic treatment. Thymoquinone, an active ingredient of Nigella sativa, has an antimicrobial effect on both gram-negative and positive bacteria, including E. faecalis. Purpose: This study aimed to evaluate the inhibitory effect of calcium hydroxide combined with Nigella sativa extract and determine the best ratio for the combined material. Methods: This is an experimental study comprised of six groups (n = 4 per group) based on the material and its ratio, namely; (1) calcium hydroxide; (2) Nigella sativa extract; and groups of the combination of calcium hydroxide and Nigella sativa extract with a ratio (3) 70:30, (4) 50:50, (5) 30:70, (6) 10:90. The inhibitory effect against E. faecalis was evaluated by the agar well diffusion method in Muller–Hinton agar. Observation of the inhibitory zone was performed on the first, third, and seventh days. The collected data were analysed by a one-way ANOVA and LSD post hoc test. Results: Calcium hydroxide has the highest inhibitory effect, and the combination of Nigella sativa extract with calcium hydroxide ratio 50:50 was second. The inhibitory zone of these two groups was significantly higher than in any other group (p<0.05). Conclusion: Nigella sativa extract combine with calcium hydroxide did not enhance calcium hydroxide’s antimicrobial property against E. faecalis. An equal amount of Nigella sativa and calcium hydroxide is the best combination ratio, with a stable effect for up to seven days.